Understanding US Immigration Detention: Reaffirming Rights and Addressing Social-Structural Determinants of Health - SAADI, ALTAF; DE TRINIDAD YOUNG, MARIA-ELENA; PATLER, CAITLIN; ESTRADA, JEREMIAS LEONEL; VENTERS, HOMER (Health and human rights, 2020)
A crisis of mass immigration detention exists in the United States, which is home to the world’s largest immigration detention system. The immigration detention system is legally classified as civil, rather than criminal, and therefore non-punitive. Yet it mimics the criminal incarceration system and holds detained individuals in punitive, prison-like conditions. Within immigration detention centers, there are increasing reports and recognition of civil and human rights abuses, including preventable in-custody deaths. In this paper, we propose understanding the health impacts of detention as an accumulation of mental and physical trauma that take place during the entirety of a detained immigrant’s experience, from migration to potential deportation and removal. Further, we explore the social-structural determinants of health as they relate to immigration detention, contextualize these determinants within a human rights framework, and draw parallels to the larger context of US mass incarceration. Realizing the right to health requires addressing these social-structural determinants of health. For the care of immigrant patients to be effective, clinicians and public health professionals must incorporate an awareness of the health risks of the immigration detention system into trauma- and human rights-informed models of care during and after detention.